Risk Factors and Outcomes of Early Relapse After Curative Resection of Intrahepatic Cholangiocarcinoma - Yang, Hua; Wang, Jie; Li, Zehuan; Yang, Yi; Yang, Liuxiao; Zhang, Yong; Shi, Yinghong; Cao, Ya; Zhou, Jian; Wang, Zheng; Chen, Qing (Frontiers in Oncology, 2019)
Early relapse after hepatectomy for intrahepatic cholangiocarcinoma (ICC) has a tremendous influence on the long-term survival outcomes of ICC patients. The purpose of our study was to investigate risk factors for early tumor relapse and confirm whether early relapse was correlated with ICC patients' long-term survival outcomes. Three hundred and twenty-two consecutive ICC patients undergoing partial hepatectomy at Liver Surgery Department of Zhongshan Hospital (Fudan University, Shanghai, China) between January 2005 and December 2011 were included in this retrospectively study. The definition of early relapse had been described as tumor relapse within 24 months after hepatectomy in ICC patients. We identified a total of 168 ICC patients with early relapse and 23 ICC patients with late relapse after hepatectomy. From the time of relapse, the long-term survival outcomes were worse among patients who had early vs. late relapse (median OS 16.5 vs. 44.7 months, respectively; P < 0.0001). The overall survival of the early relapse group was lower than that of the late relapse group (P < 0.0001). Multivariate Cox regression analysis indicated that multiple tumors (hazard ratio [HR], 1.951; 95% CI, 1.382–2.755; P < 0.001), lymphonodus metastasis (HR, 1.517; 95% CI, 1.061–2.168; P = 0.022), and higher serum CA19-9 levels (HR, 1.495; 95% CI, 1.095–2.039; P = 0.011) were independent risk factors of early relapse. Moreover, multiple tumors (HR, 1.641; 95% CI, 1.120–2.406; P = 0.011), lymphonodus metastasis (HR, 2.008; 95% CI, 1.367–2.949; P < 0.001), elevated NLR (HR, 1.921; 95% CI, 1.331–2.774; P < 0.001) and higher serum CA19-9 levels (HR, 1.990; 95% CI, 1.409–2.812; P < 0.001) were independent predictors of overall survival for ICC patients with early relapse. Collectively, our findings demonstrated that multiple tumors, lymphonodus metastasis, and higher serum CA19-9 levels were associated with the increased risks of early relapse and worse prognoses of ICC after curative-intent resection.